Importance of old rural areas of Lubuskie Lakeland and central Pomerania for maintenance of vegetation diversity - Wojterska, Maria; Brzeg, Andrzej; Jasińska, Katarzyna (Biodiversity: Research and Conservation, 2016)
The study areas, located in northern and western Poland, comprised 30 villages of the Lubuskie Lakeland region and 18 in central Pomerania. A total number of recorded associations and local communities of similar rank was counted as 243. In the list prevailed natural and seminatural communities. The endangered associations composed about 47.3% of the whole list of communities. Altogether, 8 communities, assessed as directly endangered, occurred in the villages or their vicinity. Comparison of plant communities of both regions revealed that the structure of vegetation shows many affinities, while the differences are more of qualitative than quantitative character. The diversity of vegetation of rural landscapes was slightly higher in the central Pomerania. The rural landscape of Lubuskie Lakeland was more transformed, richer in ruderal communities, whereas in Pomerania more represented were natural and seminatural communities. The rural landscape of both studied areas is still rich and diversified but recently undergoes transformations leading to its impoverishment and unification as a result of either abandonment of land use or its intensification and new forms of human impact.